2013
DOI: 10.4103/0975-5950.117825
|View full text |Cite
|
Sign up to set email alerts
|

Application of PRF in surgical management of periapical lesions

Abstract: Aims and Objectives:Platelet rich fibrin is widely used in stimulation and acceleration of soft tissue and bone healing because of local and continuous delivery of growth factors and proteins, mimicking the needs of the physiological wound healing and reparative tissue processes. This article will serve to introduce a second generation platelet concentrate, platelet-rich fibrin (PRF).Materials and Methods:Fifteen cases are presented in which conventional endodontic therapy failed to resolve the problem and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 8 publications
4
33
0
1
Order By: Relevance
“…All of them were radiological diagnosed to have bilaterally impacted mandibular third molar. Smita Singh et al (2013)[11] took a sample size of 15 for their study on application of PRF in surgical management of periapical lesions. Mozzati et al (2007)[12] in their study took a sample size of 5.…”
Section: Discussionmentioning
confidence: 99%
“…All of them were radiological diagnosed to have bilaterally impacted mandibular third molar. Smita Singh et al (2013)[11] took a sample size of 15 for their study on application of PRF in surgical management of periapical lesions. Mozzati et al (2007)[12] in their study took a sample size of 5.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al used platelet rich fibrin for stimulation and acceleration of soft tissue and bone healing with surgical procedure combined and it proved to be very successful. Six months after surgery, complete bone regeneration was found in all patients [19].…”
Section: Discussionmentioning
confidence: 87%
“…The results of the presented research indicate that the application of CGF material in oral surgery procedures such as teeth extractions reduces the intensity of post-operative alignments. Also Singh et al and Meshram et al concluded that PRF offers many advantages such as decrease of the frequency of intraoperative and postoperative bleeding, promotion of more rapid soft tissue healing and rapid vascularization of the healing tissue by delivering growth factors [7,11]. In conclusion, use of CGF in intraosseous bone defects can result in successful bone formation as it promotes faster regeneration because of gradual release of growth factors lodged in the fibrin matrix.…”
Section: Healing Process Pointsmentioning
confidence: 97%